Patients with malignant lymphoma and HIV infection experiencing remission after first-line treatment have an excellent prognosis - Kriegsmann, Katharina; Klee, Julia; Hensel, Manfred; Buß, Eike Christian; Kriegsmann, Mark; Cremer, Martin; Ho, Anthony Dick; Egerer, Gerlinde; Wuchter, Patrick; Witzens-Harig, Mathias (Clinical lymphoma, myeloma & leukemia, 2019)
Background - Malignant lymphoma is still the leading cause of death among AIDS-related diseases. - Patients and Methods - We performed a retrospective analysis of 50 HIV-positive lymphoma patients. The median interval between HIV and malignant lymphoma diagnosis was 4 years. Eight patients (16%) had Hodgkin lymphoma and 42 (84%) non-Hodgkin lymphoma. Among non-Hodgkin lymphoma patients, diffuse large B-cell lymphoma (n = 18, 42%), Burkitt lymphoma (n = 11, 26%), and plasmoblastic lymphoma (n = 5, 12%) were the most frequent entities. - Results - Lymphoma was treated according to standard protocols. Forty-four patients (88%) received combination antiretroviral therapy, 2 (4%) were not treated, and in 4 (8%) the HIV treatment status was not clarified. Response to first-line therapy was complete response (CR) in 24 (56%), partial response (PR) in 15 (35%), and stable disease in 1 (2%). Three patients (7%) developed progressive disease, and 9 (18%) experienced relapse after CR or PR. At a median observation period of 31 (range, 0.4-192) months, the 1-, 2-, and 5-year overall survival was 87%, 79%, and 76%, respectively. At univariate analysis, remission status after first-line treatment was predictive of outcome, as the 2-year overall survival was 95%, 66%, and 0 for patients with CR, with PR, and with progressive disease (P < .001). Results of the multivariate analysis revealed lactate dehydrogenase concentration at lymphoma diagnosis (P = .046) and relapse (P = .050) to be independent factors for overall survival. - Conclusion - First-line treatment of lymphoma in HIV positive patients is crucial. Patients who experienced and maintained a first CR had a favorable prognosis.
Gesehen am 21.11.2019